2007
DOI: 10.1177/0269216306073127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pain in hospitalised cancer patients in Norway: a national survey

Abstract: Purpose: Pain severely impairs health-related quality of life and is a feared symptom among cancer patients. Unfortunately, patients often do not receive optimal care. We wanted to evaluate the quality of cancer pain treatment in Norwegian hospitals. Patients and methods: A one-day prevalence study targeting hospitalised cancer patients above 18 years of age was performed. A questionnaire based on the Brief Pain Inventory was used, and additional information regarding sex, age, diagnosis, break through pain (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 17 publications
6
31
0
1
Order By: Relevance
“…Bandieri et al [25] found that early access to an integrated palliative care team was associated with a 31% reduced risk of suffering from severe pain. However, Holtan et al [26] found that inadequate pain management, for example the underuse of analgesics, was often caused by a lack of basic knowledge and failure to perform individual pain assessment. Deterioration was the other common reason for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Bandieri et al [25] found that early access to an integrated palliative care team was associated with a 31% reduced risk of suffering from severe pain. However, Holtan et al [26] found that inadequate pain management, for example the underuse of analgesics, was often caused by a lack of basic knowledge and failure to perform individual pain assessment. Deterioration was the other common reason for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer pain considerably restricts patients" daily living activities (15,17,24). Therefore, it is a natural consequence that patients state that activites such as moving, eating and drinking increase the pain that patients experience.…”
Section: Discussionmentioning
confidence: 99%
“…concentrate and an increased level of fatigue and anxiety resulting in a decline in quality of life (13,14,15). Alongside this, cancer pain has undesirable effects on the families of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a category of patients, also, cancer disease may have been successfully cured, but the chronic pain disease may still persist. Even in countries with advanced health care systems, the current prevalence of persisting pain in cancer patients remains overall high (52%) (2). The prevalence of pain in patients with advanced disease, such as in patients with metastases to the bones, has been even higher, reaching 61%.…”
Section: The Epidemiology Of Cancer Pain Todaymentioning
confidence: 99%